High-conductivity low-grinding gallium-based liquid metal electric contact composite material and preparation method thereof
By using gallium-based liquid metal in electrical contact materials to fill the rough peak gap of the current-carrying friction interface, and combining conductive ceramics and conductive lubricating phases, the problem that existing materials are difficult to take into account high conductivity and low wear under high vacuum conditions, achieving higher current-carrying friction performance and longer service life.
Patent Information
- Application Number
- CN202510293384.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
It is difficult for existing electrical contact materials to achieve high conductivity and low wear performance at the same time under high current-carrying and high vacuum conditions, and the current-carrying friction interface is prone to severe wear and deterioration at high current-carrying.
Gallium-based liquid metal is used as the conductive additive phase to fill the rough peak gap of the current-carrying friction interface, increase the actual current-carrying area, and use conductive ceramics as the matrix material, and combine conductive lubricating phases to improve the wear resistance of the material.
It achieves a balance between high conductivity and low wear performance of electrical contact materials, improves current-carrying friction performance, reduces contact resistance and wear rate, and extends the reliable service life of electrical contact devices.
Smart Images

Figure CN119811738A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrical contact composite materials, and relates to an electrical contact composite material and a preparation method thereof. Specifically, the present invention relates to a conductive ceramic-based composite material having both high conductivity and wear resistance, using gallium-based liquid metal as a conductive additive phase to increase the actual current-carrying area of the interface, and a preparation method thereof. Background Art
[0002] Current-carrying friction refers to the friction generated between interfaces in relative motion while current is being transmitted. It is widely found in high-end equipment in the fields of aerospace, advanced weapons, transportation, new energy, etc., including conductive rings in spacecraft and floating wind turbines, electromagnetic railgun armatures / rails, electric locomotive pantographs / contact networks, etc. The above-mentioned application fields urgently need to solve the problem of high conductivity and low wear of key moving pairs under extremely harsh working conditions (high current / high vacuum, etc.), which is difficult to meet with the existing current-carrying friction system. For example, the contact resistivity of metal-based materials is as low as ~10 -12 Ωm 2 , but the wear rate is as high as ~10 -3 mm 3 N -1 m -1 ; Other new materials such as diamond-like carbon-based coatings and conductive two-dimensional materials can have wear rates as low as ~10 -7 mm 3 N -1 m -1 , but the contact resistivity is as high as ~10 -10 Ωm 2 The interface current density of the macroscopic current-carrying friction system is generally <300MA / m 2 .
[0003] Although metal materials with good electrical conductivity and anti-friction and anti-wear materials can be combined together through material composites to regulate the electrical conductivity and wear resistance of the materials, it is still difficult to develop electrical contact materials with both high conductivity and low wear properties.
[0004] In addition, when the current-carrying friction interface carries a large current, the interface will also undergo severe wear and deterioration due to factors such as Joule temperature rise and arc erosion, resulting in further degradation of interface performance. This greatly restricts the improvement of the life and reliability of future high-power equipment.
[0005] Existing current-carrying friction materials focus on improving the conductivity or wear resistance of the material itself, but pay insufficient attention to the physical and chemical state of the material's current-carrying friction interface. They all require sacrificing one aspect of the material's mechanical / electrical properties in exchange for an improvement in another aspect of the performance, and are unable to fundamentally solve the problem of balancing conductivity and wear resistance.
[0006] The surface of the electrical contact material is composed of many rough peaks at the microscopic level, and the actual contact area accounts for only a small part of the macroscopic contact area, which introduces a higher contact resistance at the contact interface. In addition, during the current-carrying friction process, changes in the interface contact state will also cause problems such as rough peak separation and arc ablation, resulting in contact resistance fluctuations and even current transmission failure. Limited by the degradation of the interface state under high current-carrying conditions, the limiting current density of electrical contact materials cannot be further improved, and these problems cannot be solved by existing technologies. Summary of the invention
[0007] Problem that the invention aims to solve The object of the present invention is to provide an electrical contact composite material and a preparation method thereof which can solve the problem that electrical contact materials have always been difficult to achieve both high conductivity and low wear performance.
[0008] Solutions for solving problems The electrical contact composite material of the present invention uses gallium-based liquid metal as a conductive additive phase to fill the rough peak gaps of the current-carrying friction interface to greatly increase the actual current-carrying area, and the material uses conductive ceramics with good wear resistance as a matrix, thereby solving the above technical problems.
[0009] Specifically, the present invention provides an electrical contact composite material, which comprises: 85% to 98% by mass of a matrix material; and 1% to 5% by mass of a conductive additive phase, wherein the matrix material is a conductive ceramic and the conductive additive phase is a gallium-based liquid metal.
[0010] According to the electrical contact composite material of the present invention, the conductive ceramic is selected from at least one of tungsten carbide, titanium carbide, titanium nitride and titanium aluminum carbide.
[0011] According to the electrical contact composite material of the present invention, the gallium-based liquid metal is selected from at least one of pure metallic gallium, gallium-indium alloy, gallium-indium-tin alloy and gallium-indium-tin-zinc alloy.
[0012] According to the electrical contact composite material of the present invention, the gallium-based liquid metal is a gallium-indium alloy, wherein the mass ratio of gallium to indium is Ga:In=70:30-80:20.
[0013] According to the electrical contact composite material of the present invention, the electrical contact composite material further comprises 1 mass % to 10 mass % of a conductive lubricating phase, and the conductive lubricating phase is at least one selected from graphite, niobium diselenide and nickel ditelluride.
[0014] The electrical contact composite material according to the present invention has a wear rate of 1×10 -6 mm 3 N -1 m -1Below, the contact resistance is 1×10 -11 Ωm 2 Below, the interface current density is 500MA / m 2 above.
[0015] The electrical contact composite material according to the present invention has a wear rate of 1×10 -6 mm 3 N -1 m -1 Below, the contact resistance is 6×10 -11 Ωm 2 Below, the interface current density is 500MA / m 2 above.
[0016] The present invention also provides a method for preparing the electrical contact composite material of the present invention, the preparation method comprising the following steps: (1) Mixing: mixing the conductive ceramic powder and the gallium-based liquid metal raw material to obtain a composite powder; (2) hot pressing and sintering: placing the composite powder obtained in step (1) in a mold for hot pressing and sintering, and obtaining a sintered blank after cooling; (3) Grinding and polishing: Grinding and polishing the sintered blank obtained in step (2) to obtain an electrical contact composite material.
[0017] According to the preparation method of the present invention, conductive lubricating phase powder is further added in step (1).
[0018] According to the preparation method of the present invention, the atmosphere of hot pressing sintering is argon atmosphere, the sintering pressure of hot pressing sintering is 40~200MPa, the sintering temperature is 1000~1800℃, the insulation time is 10~30min, and the particle size of the conductive ceramic powder is 50~400nm.
[0019] Effects of the Invention The technical solution of the present invention has the following beneficial effects: The electrical contact composite material of the present invention achieves both high conductivity and low wear performance, improves the limiting current-carrying density of the electrical contact material, and is of great significance to the performance improvement of electrical contact devices; the present invention proposes for the first time a material design that improves the current-carrying friction performance of the electrical contact material by compounding gallium-based liquid metal into the electrical contact material and increasing the actual current-carrying area of the interface by a small amount of precipitation of liquid metal during the current-carrying friction process, as well as a preparation method for related materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the current-carrying friction interface of the electrical contact composite material of the present invention.
[0021] Figure 2is a scanning electron microscope (SEM) image of the surface of the electrical contact composite-I.
[0022] Figure 3 This is the variation curve of friction coefficient and contact resistance during the current-carrying friction test of electrical contact composite material-I. DETAILED DESCRIPTION
[0023] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0024] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0025] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0026] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0027] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0028] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoint numerical values A and B.
[0029] In this specification, "room temperature" means "20 to 40°C".
[0030] Electrical contact composites The present invention provides an electrical contact composite material comprising conductive ceramic as a matrix material and gallium-based liquid metal as a conductive additive phase. The electrical contact composite material has both high conductivity and wear resistance and will not cause arc erosion and severe wear when high current is carried during use.
[0031] During the current-carrying friction process of the electrical contact composite material of the present invention, as the base material wears, a small amount of gallium-based liquid metal precipitates and fills the rough peak gaps in the wear scar area, thereby greatly increasing the actual current-carrying area of the interface, reducing the contact resistance and its fluctuation, and alleviating the problem of aggravated material wear caused by Joule heat temperature rise.
[0032] Gallium-based liquid metal will chemically react with most metal materials such as copper and silver to form intermetallic compounds or dissolve in each other. The high temperature environment during hot pressing and sintering will also aggravate this process, which makes it difficult to compound gallium-based liquid metal into the interior of the metal matrix. Therefore, the present invention uses a conductive ceramic that does not react or dissolve with gallium-based liquid metal as a matrix, and at the same time uses a high-strength ceramic material to make the obtained composite material have excellent wear resistance.
[0033] In some preferred embodiments, the electrical contact composite material of the present invention further comprises a conductive lubricating phase, which can reduce the friction coefficient of the current-carrying friction interface and further reduce the wear rate of the material.
[0034] Figure 1 This is a schematic diagram of the mechanism by which the gallium-based liquid metal at the current-carrying friction interface fills the rough peak gaps in the wear scar area to increase the actual current-carrying area, and the conductive lubricating phase plays a lubricating role. During the friction process, the gallium-based liquid metal inside the composite material is slowly and slightly released at the interface, filling the rough peak gaps in the wear scar area to promote the formation of conformal contact, greatly increasing the actual current-carrying area; the conductive lubricating phase forms a heterogeneous weak shear slip surface to reduce friction.
[0035] Hereinafter, the composite material for electrical contact of the present invention will be described in detail.
[0036] Base material The electric contact composite material of the present invention comprises a matrix material, and the matrix material is a conductive ceramic with good wear resistance.
[0037] The conductive ceramic has high strength, so that the final electrical contact composite material has excellent wear resistance. The conductive ceramic can be at least one selected from tungsten carbide, titanium carbide, titanium nitride and titanium aluminum carbide. In some embodiments, the conductive ceramic is preferably tungsten carbide, which has high hardness, wear resistance, and high melting point, and can effectively improve the wear and arc ablation problems of the electrical contact material during the current-carrying friction process.
[0038] Due to the high hardness and low deformation capacity of tungsten carbide materials, the rough peaks on its surface are easily separated during the current-carrying friction process, resulting in large fluctuations in dynamic contact resistance. Therefore, tungsten carbide is rarely used as the matrix of electrical contact materials in the prior art. In the present invention, tungsten carbide is preferably used as the matrix material and gallium-based liquid metal is added thereto as a conductive additive phase. The good deformation capacity of gallium-based liquid metal is used to fill the rough peak gaps at the tungsten carbide interface, which can effectively increase the actual current-carrying area of the interface and the limiting current-carrying density of the tungsten carbide material, thereby achieving a balance between the conductive performance and wear resistance of the electrical contact composite material.
[0039] In some embodiments, the content of the matrix material in the electrical contact composite material is 85 mass % to 98 mass %, for example, 88 mass %, 91 mass %, or 94 mass %.
[0040] Conductive additives The electrical contact composite material of the present invention comprises a conductive additive phase, wherein the conductive additive phase is a gallium-based liquid metal. Gallium-based liquid metal is a type of metal material with a melting point at or below room temperature, and has the characteristics of low toxicity, high fluidity, low saturated vapor pressure, and the like.
[0041] Gallium-based liquid metal does not react or dissolve with conductive ceramics, so in the electrical contact composite material described in the present invention, the gallium-based liquid metal as a conductive additive phase is stored in the conductive ceramic as a matrix material. During the current-carrying friction process, according to the interface state, the gallium-based liquid metal can be adaptively precipitated and filled into the gaps of the rough peaks of the current-carrying friction interface, thereby greatly increasing the actual current-carrying area at the interface, avoiding arc erosion and increased wear caused by the separation of rough peaks, reducing the contact resistance fluctuations during the current-carrying friction process, and thus extending the reliable service life of the electrical contact composite material.
[0042] In some embodiments, the gallium-based liquid metal is preferably selected from at least one of pure metallic gallium, a gallium-indium alloy, a gallium-indium-tin alloy, and a gallium-indium-tin-zinc alloy, more preferably a gallium-indium alloy, wherein the mass ratio of gallium to indium is Ga:In=70:30~80:20, for example, 72:28, 74.5:25.5, 75.5:24.5, 78:22, and further more preferably a eutectic gallium-indium alloy, wherein the mass ratio of gallium to indium is Ga:In=75.5:24.5.
[0043] In some embodiments, the content of the conductive additive phase in the electrical contact composite material is 1 mass % to 5 mass %, for example, 2 mass %, 3 mass %, or 4 mass %.
[0044] Conductive lubricating phase The electrical contact composite material of the present invention may further include a conductive lubricating phase, which can reduce the friction coefficient of the current-carrying friction interface and further reduce the wear rate of the material at the low shear interface formed at the electrical contact interface, thereby alleviating the problem of increased contact resistance caused by wear. The conductive lubricating phase may be at least one selected from graphite, niobium diselenide and nickel ditelluride.
[0045] In some embodiments, the conductive lubricating phase is preferably graphite.
[0046] In some embodiments, the content of the conductive lubricating phase in the electrical contact composite material is 1 mass % to 10 mass %, for example, 4 mass % or 7 mass %.
[0047] The hardness of the electrical contact composite material of the present invention is above 800 HV, and the material wear rate during use is 1×10 -6 mm 3 N -1 m -1 Below, the contact resistance is 6×10 -11 Ωm 2 Below, for example, 1×10 -11 Ωm 2 Below, the interface current density is 500MA / m 2 The above results show that the electrical contact composite material of the present invention can achieve both high electrical conductivity and low wear performance.
[0048] The hardness test method is as follows: use a Vickers hardness tester to test, with a test force of 0.3 kgf and a holding time of 15 seconds. Measure at least 3 different locations and take the average value as the final hardness value.
[0049] The test method of material wear rate and contact resistivity is as follows: the electrical contact composite material of the present invention uses tungsten steel balls as the grinding pair and performs current-carrying friction test in a vacuum environment. The test parameters are: temperature 27°C, vacuum degree <1×10 -3 Pa, the motion mode is continuous rotation, the load is 1.5N, the current is 2A, and the speed is 24rpm. Method for preparing electrical contact composite material The present invention also provides a method for preparing the electrical contact composite material, which comprises the following steps: (1) Mixing: mixing the conductive ceramic powder and the gallium-based liquid metal raw material to obtain a composite powder; (2) hot pressing and sintering: placing the composite powder obtained in step (1) in a mold for hot pressing and sintering, and obtaining a sintered blank after cooling; (3) Grinding and polishing: Grinding and polishing the sintered blank obtained in step (2) to obtain an electrical contact composite material.
[0051] Each step is described in detail below.
[0052] (1) Mixing In this step, the required mass of conductive ceramic powder and gallium-based liquid metal raw material are mixed evenly by mechanical stirring according to the proportion of each component in the finished product to prepare a composite powder to be hot-pressed and sintered. In this step, the conductive ceramic powder can separate the gallium-based liquid metal raw material droplets so that they are evenly dispersed in the mixed system.
[0053] In some embodiments, the conductive ceramic powder is preferably tungsten carbide powder. In some embodiments, the particle size of the conductive ceramic powder is preferably 50 to 400 nm, for example, 60 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm. Nanoscale powders can reduce the temperature required for sintering, reduce the vaporization of liquid metal during sintering, and avoid the formation of defects such as pores inside the material.
[0054] In some embodiments, the gallium-based liquid metal raw material is preferably selected from at least one of pure metallic gallium, gallium-indium alloy, gallium-indium-tin alloy, and gallium-indium-tin-zinc alloy. In some embodiments, the gallium-based liquid metal raw material is more preferably a gallium-indium alloy, wherein the mass ratio of gallium to indium is Ga:In=70:30~80:20, for example, 72:28, 74.5:25.5, 75.5:24.5, 78:22. In some embodiments, the gallium-based liquid metal is further more preferably a eutectic gallium-indium alloy, wherein the mass ratio of gallium to indium is Ga:In=75.5:24.5, and the melting point of the alloy is 15.7°C, which is convenient for the mixing step at room temperature.
[0055] In some embodiments, conductive lubricating phase powder is further added in the mixing step to further reduce the friction coefficient and wear rate of the composite material. In some embodiments, the conductive lubricating phase powder is preferably graphite powder. In some embodiments, the particle size of the conductive lubricating phase powder is preferably 1 to 10 μm, for example, 1.6 μm, 2 μm, 4 μm, 6 μm, 8 μm.
[0056] (2) Hot pressing sintering In this step, the composite powder obtained in step (1) is placed in a mold for hot pressing and sintering and heat preservation, and a sintered blank is obtained after cooling; In some embodiments, the hot pressing sintering atmosphere is an inert gas atmosphere, preferably an argon atmosphere. The use of an argon atmosphere can reduce the vaporization of the gallium-based liquid metal raw material during high-temperature sintering, and at the same time play a protective role to avoid oxidation problems of the gallium-based liquid metal.
[0057] In some embodiments, the sintering pressure is preferably 40-200 MPa, the sintering temperature is preferably 1000-1800° C., and the sintering holding time is preferably 10-30 min.
[0058] In some embodiments, the cooling process is preferably furnace cooling.
[0059] (3) Grinding and polishing The sintered blank obtained in step (2) is ground and polished to obtain an electrical contact composite material.
[0060] In some embodiments, in the grinding and polishing step, the sintered green body is preferably ground and polished using a polishing machine, sandpaper, a polishing cloth and a polishing liquid.
[0061] In some embodiments, after the grinding and polishing step, the surface roughness of the sintered compact can be reduced to less than Ra 0.2 μm and defects on the surface layer of the sintered compact can be removed.
[0062] The electrical contact composite material prepared by the present invention has very low contact resistivity and wear rate in a vacuum environment. Gallium-based liquid metal is released in small amounts at the contact interface during current-carrying friction, effectively filling the rough peak gaps in the wear scar area, greatly improving the electrical contact performance of the system. Example
[0063] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially. The test methods not described in detail in the examples are all conventional test methods in the art.
[0064] Example 1
[0065] The electrical contact composite material-I of Example 1 was prepared as follows, wherein the equipment used, such as a mixer and a hot press furnace, are those known to those skilled in the art.
[0066] (1) Mixing: In the prepared electrical contact composite material, tungsten carbide accounts for 95% by mass, and the remainder is eutectic gallium-indium alloy. The mass ratio of gallium to indium in the alloy is Ga:In=75.5:24.5. Weigh the required tungsten carbide and gallium-indium alloy raw materials according to the above ratio and add them to the mixer. The particle size of the selected tungsten carbide powder is 50nm. In the mixer, the tungsten carbide powder and the gallium-indium alloy are mixed evenly by mechanical stirring until the mixed system is in powder form, and there are no aggregated eutectic gallium-indium alloy droplets on a macro scale, so as to facilitate subsequent hot pressing sintering. Tungsten carbide powder can effectively separate the gallium-indium alloy droplets, so that the mixed system is in a solid powder state.
[0067] (2) Hot pressing sintering: Select a hot pressing mold of appropriate size according to the size of the finished product, and weigh the mixed powder prepared in the above steps according to the mass of the finished product. Add the mixed powder to the mold and put it into a hot pressing furnace. Sinter and keep it warm for 15 minutes in an argon atmosphere, a sintering pressure of 50 MPa and a sintering temperature of 1400°C. After sintering, cool the mold and the sample in it to below 40°C and take them out.
[0068] (3) The sample surface was polished using a polishing machine, sandpaper, polishing cloth and polishing liquid to reduce the surface roughness of the sintered blank to less than Ra 0.2 μm and remove defects on the surface of the sintered blank. The obtained sample was recorded as electrical contact composite material-I.
[0069] Example 2
[0070] An electrical contact composite material-II was prepared according to the method of Example 1, except that: in the prepared electrical contact composite material, tungsten carbide accounted for 85% by mass, graphite accounted for 10% by mass, and the remainder was eutectic gallium-indium alloy. The particle size of the graphite powder selected during the preparation was 1.6 μm. The obtained sample was recorded as electrical contact composite material-II.
[0071] Performance Testing SEM and Energy Dispersive Spectroscopy (EDS) For SEM testing, the instrument model is Gemini 300, ZEISS (Germany); the acceleration voltage is 3 kV; the testing method is to take the electrical contact composite material sample and stick it to the conductive glue on the sample stage to photograph the sample morphology.
[0072] For EDS testing, the instrument model is XPLORE30, OXFORD (UK); the acceleration voltage is 15kV; the testing method is to take the electrical contact composite material sample and stick it to the conductive glue on the sample table, and perform energy spectrum testing to measure the elemental composition and relative content of the sample.
[0073] The SEM image of the surface of the electrical contact composite material-I is as follows Figure 2As shown in the figure, tungsten carbide (WC) is the matrix material, and eutectic gallium indium alloy (EGaIn) is dispersed in the micropores of the tungsten carbide matrix as a conductive additive phase.
[0074] The microstructure and elemental composition of the wear scar were characterized by SEM and EDS techniques, and it was found that the content of gallium and indium elements inside the wear scar was significantly higher than that outside the wear scar, indicating that during the current-carrying friction process, the gallium-based liquid metal effectively filled the rough peak gaps in the wear scar area, and only a small amount of it precipitated in the wear scar area.
[0075] Triboelectric conductivity test The current-carrying friction performance of the prepared electrical contact composite material-I and electrical contact composite material-II was tested using a tungsten steel (grade YG6) ball with a diameter of 8 mm as the current-carrying friction pair. The test parameters were vacuum degree <1×10 -3 Pa, the motion mode is continuous rotation, the load is 1.5N, the current is 2A, and the speed is 24rpm.
[0076] Figure 3 It is a curve of the change of friction coefficient and contact resistance over time in the current-carrying friction test of the electrical contact composite material-I. Combined with the data of the change of contact resistance over time, it can be seen that after adding gallium-based liquid metal, the actual current-carrying area of the interface is greatly improved, which effectively reduces the contact resistance of the composite material and alleviates the aggravating effect of Joule heat temperature rise on wear.
[0077] Material wear rate and contact resistivity After the friction conductivity test, the samples were taken out of the vacuum chamber, and the three-dimensional morphology of the wear scars on the surfaces of the electrical contact composite materials-I and electrical contact composite materials-II were measured by white light interferometry and the wear rate was calculated. At the same time, the width of the wear scars was determined to calculate the contact resistivity.
[0078] Regarding the measurement of the three-dimensional morphology of wear scars on the composite surface by white light interferometry, the instrument model used is NexView, ZYGO Company (USA); the vertical resolution is 0.1nm, and the relevant test method is to take an electrical contact composite material sample and place it on the instrument sample stage and level it, and measure the three-dimensional morphology near the wear scar area on the sample surface to obtain the wear volume.
[0079] The calculation method of contact resistivity is: contact resistance × π × (wear scar width) 2 / 4.
[0080] The calculation method of interface current density is: current / (π×(wear scar width) 2 / 4) The test results show that the wear rate of the electrical contact composite material-I is 7×10 -7 mm 3 N-1 m -1 The contact resistance is 9×10 -12 Ωm 2 The average friction coefficient is 0.28, and the interface current density is 520MA / m 2 ; The wear rate of the electrical contact composite material-II is 5×10 -7 mm 3 N -1 m -1 The contact resistance is 6×10 -11 Ωm 2 The average friction coefficient is 0.22, and the interface current density is 707MA / m 2 .
[0081] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0082] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrical contact composite material, characterized in that: The electrical contact composite material comprises: 85% to 98% by mass of a matrix material; and 1% to 5% by mass of conductive additive phase, Wherein, the base material is conductive ceramic, The conductive additive phase is gallium-based liquid metal.
2. The electrical contact composite material according to claim 1, characterized in that: The conductive ceramic is selected from at least one of tungsten carbide, titanium carbide, titanium nitride and titanium aluminum carbide.
3. The electrical contact composite material according to claim 1 or 2, characterized in that: The gallium-based liquid metal is selected from at least one of pure metallic gallium, gallium-indium alloy, gallium-indium-tin alloy and gallium-indium-tin-zinc alloy.
4. The electrical contact composite material according to claim 1 or 2, characterized in that: The gallium-based liquid metal is a gallium-indium alloy, wherein the mass ratio of gallium to indium is Ga:In=70:30-80:
20.
5. The electrical contact composite material according to claim 1 or 2, characterized in that: The electrical contact composite material further comprises 1 mass % to 10 mass % of a conductive lubricating phase, wherein the conductive lubricating phase is at least one selected from graphite, niobium diselenide and nickel ditelluride.
6. The electrical contact composite material according to claim 1 or 2, characterized in that: The wear rate of the electrical contact composite material is 1×10 -6 mm 3 N -1 m -1 Below, the contact resistance is 1×10 -11 Ωm 2 Below, the interface current density is 500MA / m 2 above.
7. The electrical contact composite material according to claim 5, characterized in that: The wear rate of the electrical contact composite material is 1×10 -6 mm 3 N -1 m -1 Below, the contact resistance is 6×10 -11 Ωm 2 Below, the interface current density is 500MA / m 2 above.
8. A method for preparing the electrical contact composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Mixing: mixing the conductive ceramic powder and the gallium-based liquid metal raw material to obtain a composite powder; (2) hot pressing and sintering: placing the composite powder obtained in step (1) in a mold for hot pressing and sintering, and obtaining a sintered blank after cooling; (3) Grinding and polishing: Grinding and polishing the sintered blank obtained in step (2) to obtain the electrical contact composite material.
9. The method for preparing the electrical contact composite material according to claim 8, characterized in that: In the step (1), conductive lubricating phase powder is further added.
10. The method for preparing the electrical contact composite material according to claim 8 or 9, characterized in that: The atmosphere of the hot pressing sintering is an argon atmosphere, the sintering pressure of the hot pressing sintering is 40-200 MPa, the sintering temperature is 1000-1800° C., the holding time is 10-30 min, and the particle size of the conductive ceramic powder is 50-400 nm.
Citation Information
Patent Citations
Electric contact material
CN103108968A
Modified liquid metal composite material capable of being directly formed and preparation method thereof
CN113717701A
Coating containing liquid metal and preparation method and application thereof
CN115613027A
Liquid metal constant-temperature heat-conducting medium and preparation method thereof
CN115948152A
Application of copper-containing friction pair in improving wettability and / or lubricating property of gallium-based liquid metal
CN117840426A
Cited By
A negative wear ultra-wear current carrying friction pair material
CN120400742B